Badania jakościowe - kierunki rozwoju wobec wyzwań współczesnego rynku i marketingu - Mazurek-Łopacińska, Krystyna (Qualitative Research - Directions of the Development in the Face of Challenges of the Present Market and Marketing, 2006)
The article presents basic methodological approaches in qualitative research and stages of the development of this research. The evolution of methods of qualitative research toward the research based on projection techniques, creative surveys and experimental inquiry is shown. The methods of qualitative research on every stage of their realization (i.e. exploration, analysis and qualification of results) are presented.Finally, the conditions of integration and penetration of qualitative and quantitative approach are detailed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 27-38